Evaluation of a novel role proposal for the use of a physiotherapist navigator in an acute cancer care setting in Ontario: Protocol for a pilot randomized controlled trial - Holly Edward; Luciana Macedo; Sarah Wojkowski; Som D. Mukherjee; Jenna Smith-Turchyn (PLoS ONE, 2026)
Background An increasing number of Canadians are living beyond cancer, with many individuals experiencing long-lasting side effects of cancer and its treatments. Research shows that engaging in rehabilitation during and after cancer treatment can reduce side effects and improve quality of life. However, less than 30% of individuals with cancer have access to rehabilitation services. The purpose of this pilot trial is to assess the feasibility of a novel PT Navigator role in an acute cancer care setting for individuals undergoing treatment for cancer. Methods Study Design: Pilot randomized controlled trial. Eligibility: Adults aged ≥18 years who are currently undergoing cancer treatment for any type of cancer. Intervention: The intervention group includes six consultative sessions by a PT Navigator over a maximum of eighteen weeks. Randomization: Participants will be randomly allocated using a 1:1 allocation ratio to receive the intervention with the PT Navigator or usual care. Outcomes: The primary feasibility outcome is adherence rate. Secondary outcomes include recruitment rate, retention rate, satisfaction and preliminary effectiveness, including health-related quality of life, self-reported exercise volume, health care utilization, activity limitation, functional strength, exercise capacity, and overall impairment score. Analysis: Outcomes will be assessed at baseline, post-intervention, and two month follow up. Feasibility and preliminary effectiveness will be assessed using descriptive statistics. Discussion This study aims to assess the feasibility of a novel PT Navigator role in an acute cancer care setting in Ontario, Canada. This pilot trial will evaluate process and resource capabilities before testing the role within a larger scale randomized controlled trial. The overall project goal is to facilitate regular assessment by a rehabilitation professional to promote early identification of physical impairment and early intervention to manage impairment as a standard component of cancer care in Canada. Trial registration ClinicalTrials.gov ID NCT07045740 .